Relationship Between Breakfast, BMI, Sleep, and Physical Activity with Academic Achievement Among Female Students Aged 12-16 Years Old - Tawfeg A. Elhisadi; Shaima A. alshokry; Rasha F. bogeldain (African Journal of Advanced Pure and Applied Sciences, 2023)
A lack of such nourishment among adolescents can lead to various degrees of malnutrition, which may have implications on their health as well as their academic achievements (1). The human brain needs Sufficient energy specifically glucose and variety of micronutrients to perform cognitive functions. The aim of the study to identify the effect of some variables such as BMI, sleep, physical activity (PA), and breakfast on academic achievements. The study was conduct from June to July 2022 on the three intermediate schools, the subjects’ only female aged from 12-16 years, and studying between 7th to 9th classes. The questionnaire data consist of 18 questions. The number of questionnaires distributed to 300 of participants and received 236 that has been 64 excluded. The 24-hours dietary recall (24HR) used in this study to provide quantitative information on individual diets. The mean age of participants was 13.89(±1.016) range from 12 to 16 years old. The result showed that underweight, overweight and obese were 27.1%, 13.6% and 4.6% respectively. The study revealed that, 55.1% of the students slept from five to eight hours, while, 30.5%, and 14.4% slept more than 8 hours and Less than 5 hours respectively. The study revealed that normal BMI represented 54.7% when compared with obese, overweight and underweight represented 4.7%, 13.6% and 27.1% respectively. This study showed that normal BMI was major cause of good academic performance compared with unhealthy nutritional status; this difference was not strongly significant relationship (p ≥ 0.2). The study showed that 65.3% had a less physical activity (PA), and had high academic achievements among participants represented 54.2%. The results of this study were students consumed breakfast represented 83.5% compared with 16.5% skipped breakfast. Skipping breakfast was associated with poor academic performance in the present study.